2013
DOI: 10.1128/jvi.03203-12
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Thiamine Uptake and Growth of Cells by Feline Leukemia Virus Subgroup A

Abstract: Feline leukemia virus (FeLV) is still a major cause of morbidity and mortality in domestic cats and some wild cats despite the availability of relatively effective vaccines against the virus. FeLV subgroup A (FeLV-A) is transmitted in natural infections, and FeLV subgroups B, C, and T can evolve directly from FeLV-A by mutation and/or recombination with endogenous retroviruses in domestic cats, resulting in a variety of pathogenic outcomes. The cell surface entry receptor for FeLV-A is a putative thiamine tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…Future studies are required to clarify whether Cbl metabolism is altered in infected chickens. The cytopathic effects of FeLV-A, which uses the vitamin B 1 receptor, are partly caused by vitamin B 1 deficiency and can be reversed by high doses of the vitamin (54). However, the existence of a Tva-independent uptake of TC-Cbl may also ensure a sufficient delivery of Cbl in the infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are required to clarify whether Cbl metabolism is altered in infected chickens. The cytopathic effects of FeLV-A, which uses the vitamin B 1 receptor, are partly caused by vitamin B 1 deficiency and can be reversed by high doses of the vitamin (54). However, the existence of a Tva-independent uptake of TC-Cbl may also ensure a sufficient delivery of Cbl in the infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, interaction between FeLV-A Env protein and its receptor, thiamine transporter (THTR1), blocks thiamine uptake mediated by THTR1 and induces growth arrest of cells (50). It has also been shown that interaction between FeLV-C Env protein and its receptor, FLVCR-1, causes abnormal erythroid differentiation (51).…”
Section: Discussionmentioning
confidence: 99%
“…We found that lacZ(KoRV-J) interfered with FeLV-A on FEA cells (feline fibroblasts). The receptor for FeLV-A is known to be THTR1 (29,30). As shown in Fig.…”
mentioning
confidence: 99%